Environmental contamination related to SARS-CoV-2 in ICU patients. Issue 4 (10th November 2020) - Lomont, Alexandra; Boubaya, Marouane; Khamis, Warda; Deslandes, Antoine; Cordel, Hugues; Seytre, Delphine; Alloui, Chakib; Malaure, Célie; Bonnet, Nicolas; Carbonnelle, Etienne; Cohen, Yves; Nunes, Hilario; et al.
Background: The coronavirus disease 2019 (COVID-19) outbreak is a primary global concern, and data are lacking concerning risk of novel severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) environmental contamination. Objective: To identify risk factors for SARS-CoV-2 environmental contamination in COVID-19 patients admitted to the intensive care unit (ICU). Methods: A prospective single centre 1-day study was carried out in an ICU. Four surfaces (the ventilator control screen, the control buttons of the syringe pump, the bed rails and the computer table located >1 m away from the patient) were systematically swabbed at least 8 h after any cleaning process. We analysed clinical, microbiological and radiological data to identify risk factors for SARS-CoV-2 environmental contamination. Results: 40% of ICU patients were found to contaminate their environment. No particular trend emerged regarding the type of surface contaminated. Modality of oxygen support (high-flow nasal cannula oxygenation, invasive mechanical ventilation, standard oxygen mask) was not associated with the risk of environmental contamination. Univariate analysis showed that lymphopenia <0.7×10 9 ·L −1 was associated with environmental contamination. Conclusion: Despite small sample size, our study generated surprising results. Modality of oxygen support is not associated with risk of environmental contamination. Further studies are needed. Environmental contamination due to #SARSCoV2 occurs in 40% of ICU patient rooms. No difference is observed between different modalities of oxygen support (high-flow nasal cannula oxygenation, invasive mechanical ventilation, standard oxygen mask). https://bit.ly/3kgxTKx